Osteochondral Autograft Transplant as a Potential Salvage Procedure for Articular Cartilage Defects of the Lateral Compartment in Lateral Meniscus–Deficient Knees: Results From a Country With Limited Availability of Meniscal Transplant - Nishitani, Kohei (Orthop J Sports Med, 2020)
BACKGROUND: The treatment of a meniscus-deficient knee is challenging, especially when patients are young and active and are not favorable candidates for prosthetic joint replacement. HYPOTHESIS: We hypothesized that osteochondral autologous transplant (OAT) alone can be considered a salvage treatment for patients with cartilage damage of the lateral compartment of the knee, even with lateral meniscal deficiency, if the knee alignment is close to neutral. STUDY DESIGN: Case series; Level of evidence, 4. METHODS: Patients with lateral meniscal deficiency, whose femorotibial angle was 170° to 180° and who underwent OAT on the lateral compartment of the knee without concomitant realignment osteotomy, were retrospectively included in this study. The International Knee Documentation Committee (IKDC) subjective score and the Japanese Orthopaedic Association score for knee osteoarthritis (JOA knee score) were recorded. The International Cartilage Repair Society (ICRS) cartilage repair assessment was used to evaluate the repaired cartilage at second-look arthroscopy. RESULTS: The study included 10 patients (mean ± SD age, 31.7 ± 19.7 years; 3 men and 7 women) who had ICRS grade 4 cartilage lesions (mean size, 3.5 ± 1.7 cm(2)); the mean follow-up was 73.8 ± 42.5 months. From preoperative assessment to final follow-up, the mean IKDC subjective score improved significantly from 53.5 ± 10.0 to 85.4 ± 10.1, and the mean JOA knee score improved significantly from 81.0 ± 8.4 to 95.6 ± 5.3 (P = .004 for both). One patient with a femorotibial angle of 170° underwent revision distal femoral osteotomy owing to prolonged symptoms and progression of the valgus deformity, and 2 other patients with femorotibial angles of 170° and 171° also exhibited progression of valgus malalignment or low clinical scores postoperatively. Patients with a favorable femorotibial angle (174°-178°) exhibited relieved symptoms and preservation of femorotibial angle alignment within 1° of change at follow-up. At second-look arthroscopy (n = 8 patients), 6 patients had an ICRS score of nearly normal or normal. CONCLUSION: In the study patients, for which a meniscal allograft was unavailable, the OAT procedure was able to relieve the symptoms associated with cartilage lesions, even with lateral meniscal deficiency, when the femorotibial angle alignment was close to neutral.